2022
DOI: 10.4236/ojst.2022.1210026
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Bizygomatic Distance and the Width of the Upper Central Incisor in the Cameroonian Melanoderma Adult

Abstract: Bizygomatic distance is a relevant reference used to assist and to guide the choice of antero superior prosthetic teeth, especially when no information about the natural teeth was available. The aim of the present paper was to determine the distance between the canine tips from a bizygomatic distance and to estimate the width of the upper central incisor in normal-dental-facial indices of Cameroonians. Materials and methods: A cross-sectional study of 900 normal Cameroonians of both sexes was conducted. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
4
5
0
Order By: Relevance
“…21,24,25 However, few studies on the African population have shown contrasting results. 20,26 The average distance between the distal surfaces of maxillary canines is 36.013 mm, which is similar to the values reported for Croatian and Kashmiri populations. 27,28 The minor variations may be attributed to differences in measurement methods.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…21,24,25 However, few studies on the African population have shown contrasting results. 20,26 The average distance between the distal surfaces of maxillary canines is 36.013 mm, which is similar to the values reported for Croatian and Kashmiri populations. 27,28 The minor variations may be attributed to differences in measurement methods.…”
supporting
confidence: 85%
“…This scenario differed for females. Meanwhile, the finding regarding the 1:14 ratio for the BZW to central incisor width was similar to the range of 1:13-1:19 reported by Flavie et al 20 but it differed from the 1:16 ratio reported by Ellakwa et al 41 and Bozkir et al 46 To the best of our knowledge, no research has been conducted on the use of BZW to measure anterior teeth as suggested earlier. 47 Among Chinese population, wider maxillary incisors and canines were recorded, which is not in parallel with this study findings.…”
supporting
confidence: 81%
See 3 more Smart Citations